2016
DOI: 10.1057/bm.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

When is brand orientation a useful strategic posture?

Abstract: This study examines the extent to which the effect of brand orientation on sales performance is contingent upon levels of transformational leadership and inter-functional collaboration. Using primary data from 108 subsidiaries of multinational enterprises (MNEs) operating in the Commonwealth Caribbean region, the study finds that brand orientation is not directly related to sales performance. However, findings show that brand orientation is positively related to sales performance when levels of both transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…Committing resources to brand-building activities could help improve organisational performance. Empirically, the findings are supported by Boso et al (2016), Casidy et al (2018), Ciunova-Shuleska et al (2017, and Urde et al (2013). Second, the results suggest that it might be worthwhile for Malaysian tourism entrepreneurs to schedule knowledge gathering and knowledge sharing sessions (for example event sponsorships, press releases, sales promotions, and other events) with travel intermediaries, hotel associations, and other stakeholders.…”
Section: Theoretical and Practical Contributionsmentioning
confidence: 71%
See 2 more Smart Citations
“…Committing resources to brand-building activities could help improve organisational performance. Empirically, the findings are supported by Boso et al (2016), Casidy et al (2018), Ciunova-Shuleska et al (2017, and Urde et al (2013). Second, the results suggest that it might be worthwhile for Malaysian tourism entrepreneurs to schedule knowledge gathering and knowledge sharing sessions (for example event sponsorships, press releases, sales promotions, and other events) with travel intermediaries, hotel associations, and other stakeholders.…”
Section: Theoretical and Practical Contributionsmentioning
confidence: 71%
“…The study reveals the superior role of brand orientation and knowledge creation process in enhancing the organisational performance of tourist resorts. In congruence with Boso et al (2016), Casidy et al (2018), Ciunova-Shuleska et al (2017, Ismail et al (2016), andLaukkanen et al (2016), branding orientation activities are found to be an essential asset for enhancing the organisational performance of tourist resorts. Our findings emphasise the importance of knowledge creation process for tourist resorts in transmuting the knowledge pool and incorporating knowledge into business operations that enhance organisational performance (Li et al, 2009).…”
Section: Linking the Results To The Research Objectives And Past Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, research by Boso et al (2016) suggest that brand orientation on its own is not directly associated with sales performance --but that a brand orientation's effect on sales performance is accentuated when firms align it to their leadership-and structure-related activities --and when the levels of both transformational leadership and inter-functional collaboration are high. In other words, these two organisational forces are required to translate a firm's branding philosophy into sales.…”
Section: Brand Orientationmentioning
confidence: 99%
“…Since the inception of this concept, different studies have analysed the same concept in diverse contexts (Cant et al, 2013;Gromark and Melin, 2013;Jain et al, 2018;King et al, 2013;Napoli, 2006). In addition to empirical implications, several models were proposed to measure brand orientation, and its barriers, antecedents and outcomes (Apaydin, 2011;Boso et al, 2016;Harrison-Walker, 2014b;Huang and Tsai, 2013). Therefore, given the diversity of empirical and theoretical production over 20 years, we understand that it is necessary not only to systematize the content produced but also to further understand the relationship between the published research and the main thematic areas.…”
Section: Introductionmentioning
confidence: 99%